Metallic soap, method for producing the same, and cosmetics, food products, and thermoplastic resin compositions containing metallic soap.
Patent Information
- Application Number
- JP2025060364
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明の金属石鹸は、該金属石鹸の添加目的に関する添加対象の性能を向上させることができ、かつ、添加目的以外の性能を劣化させにくくするだけでなく、添加対象が厳しい環境下で保存されても添加対象の性能を劣化させにくくすることができる。 また、本発明の方法は、上記本発明の金属石鹸を、安定かつ生産性良く製造することができる。
Smart Images

Figure 2026167041000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a metal soap useful as an additive in a wide range of fields including cosmetics, foods, and thermoplastic resins, and a method for producing the same. BACKGROUND ART
[0002] Metal soaps are used as additives in a wide range of fields. For example, in the field of cosmetics, metal soaps are added to cream and gel cosmetics, powder cosmetics such as baby powder and powdery foundations, etc., for the purpose of improving lubricity and adhesion to the skin and the dispersibility of pigments. In the field of foods, metal soaps are added to foods for purposes such as improving the moldability of foods formed by compressing powders, the fluidity of powders such as wheat flour and spices, and preventing staling in bakery foods. In the field of thermoplastic resins, metal soaps are added to thermoplastic resins for the purpose of improving the dispersibility of pigments and fillers.
[0003] Metal soaps are industrially produced by a direct method in which a fatty acid is directly reacted with a metal oxide or hydroxide, or a double decomposition method in which a basic compound is added to and reacted with a fatty acid in an aqueous solution state to form a basic compound salt of the fatty acid, and a metal salt is further reacted therewith. The direct method is a method in which a fatty acid and a metal compound are maintained at a temperature equal to or higher than the melting point of the metal soap to be produced in the absence of a solvent, and water generated by the reaction is evaporated out of the system to advance the reaction and obtain the metal soap. This direct method has problems such as requiring a long reaction time, causing coloring due to thermal deterioration of the metal soap, and having a high content of free fatty acids and unreacted metal compounds. On the other hand, the double decomposition method has advantages such as producing fewer free fatty acids, yielding fine particles of metal soap that are easy to disperse, and minimizing the contamination of dissimilar metals. These advantages are due to the fact that the reaction is usually completed using a large amount of water, and in order to increase the purity of the metal soap, an excess of raw materials that can be easily removed by purification is added during production. In other words, in the neutralization step to obtain the basic compound salt of the fatty acid, an excess of the basic compound is reacted with the equivalent amount of fatty acid. A problem with the double decomposition method was that when the metal soap obtained was brought into contact with water, it would exhibit an alkaline pH of 9-10. Conventional metal soaps obtained by direct or double decomposition methods have the above-mentioned problems. Therefore, when used as additives, they can achieve their intended purpose, but may degrade the performance of other components. Patent documents 1 to 3 disclose metal soaps that can solve these problems.
[0004] Patent Document 1 discloses a thermoplastic resin composition containing a metal soap produced by a double decomposition method, specifically a fatty acid alkali compound salt obtained by reacting a monovalent alkali compound in a ratio of 0.90 moles to 0.99 moles per mole of a fatty acid having 6 to 24 carbon atoms with a divalent metal salt in an aqueous solution. Patent Document 1 states that the pH of a 2% by mass aqueous dispersion of the metal soap is 5.0 to 7.5. Furthermore, the examples in Patent Document 1 show that by adding the metal soap to a thermoplastic resin, the objective of adding it was not only achieved to improve the dispersibility of the pigment and prevent color unevenness in the resin composition, but also that the adverse effects caused by adding metal soap obtained by the secondary decomposition method were prevented. Specifically, the deterioration of the appearance of the resin composition due to yellowing of the antioxidant was reduced, and the decrease in the impact strength of the resin composition due to a decrease in the molecular weight of the thermoplastic resin was reduced.
[0005] Patent Document 2 discloses a metal soap for food additives, which is a calcium or magnesium fatty acid with 6 to 24 carbon atoms obtained by a double decomposition method, characterized in that the pH of a 2% by mass aqueous dispersion of the metal soap is 6 to less than 7, and a method for producing the metal soap, characterized in that a monovalent basic compound is reacted with 1 mole of a fatty acid with 6 to 24 carbon atoms in a ratio of 0.9 to less than 1 mole to obtain a basic compound salt of the fatty acid, and then this is reacted with a calcium salt or magnesium salt in an aqueous medium. The example in Patent Document 2 demonstrates that by adding the metal soap to food, the objective of improving the moldability of molded food products obtained by compression molding of powders and the fluidity of powdered food products was achieved. Furthermore, it shows that the adverse effects caused by the addition of metal soaps obtained by the secondary decomposition method were prevented, specifically, the fade resistance and discoloration resistance of molded food products and the discoloration resistance of powdered food products to heating were prevented.
[0006] Patent Document 3 discloses a metal soap for cosmetics, which is a magnesium fatty acid, calcium fatty acid, or zinc fatty acid having 6 to 24 carbon atoms, obtained by a double decomposition method, characterized in that the pH of a 2% by mass aqueous dispersion of the metal soap is 6 to less than 7, and a method for producing the metal soap, characterized in that a monovalent basic compound is reacted with 1 mole of a fatty acid having 6 to 24 carbon atoms in a ratio of 0.9 to less than 1 mole to obtain a basic compound salt of the fatty acid, and then this is reacted with a magnesium salt, calcium salt, or zinc salt in an aqueous medium. The example in Patent Document 3 demonstrates that by adding the metal soap to a makeup product, the objective of improving the adhesion, spreadability, finish, and longevity of the cosmetic product was achieved. Furthermore, it shows that the adverse effects caused by adding metal soaps obtained by the secondary decomposition method were prevented, specifically, that there was no change in color after storage at 35°C and 60% RH for three months. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] International Publication WO2006-006727A1 [Patent Document 2] International Publication WO2007-013655A1 [Patent Document 3] Japanese Patent Publication No. 2007-186463 [Overview of the Initiative] [Problems that the invention aims to solve]
[0008] The metal soaps described in Patent Documents 1 to 3 above have a neutral pH when dispersed in 2% by mass water. Therefore, using them as additives can improve the performance of the target material with respect to the additive's intended purpose, while minimizing the degradation of other properties. However, there is a need to provide metal soaps that are superior as additives. The present invention aims to provide a metal soap that has a neutral pH when dispersed in a 2% by mass aqueous solution, which can improve the performance of the substance to which the metal soap is added in relation to the purpose of the additive, and which not only prevents deterioration of performance other than that of the substance to which the additive is added, but also prevents deterioration of the performance of the substance to which the additive is added even when the substance is stored in a harsh environment. [Means for solving the problem]
[0009] In view of the above problems, the inventors of the present invention conducted diligent studies and found that fatty acid metal soaps having 6 to 24 carbon atoms, in which a 2% by mass aqueous dispersion has a pH of approximately neutral, and where the values of A and B, when A is the slope of the breakdown envelope of the metal soap and B is the intercept, are within a specific range, do not easily degrade the performance of the substance to which the additive is added, even when the substance is stored under harsh conditions. This led to the completion of the present invention. In other words, the present invention is as follows: [1] A fatty acid metal soap having 6 to 24 carbon atoms, wherein the pH of a 2% by mass aqueous dispersion of the metal soap is 6.0 or higher and 7.5 or lower, and when the slope of the breakdown envelope of the metal soap represented by the following formula (I) is A and the intercept is B, the values of A and B are within the following ranges. Equation (I): τ = Aσ + B 0.2 ≤ A ≤ 0.5 0.1 ≤ B ≤ 0.5 (In equation (I) above, σ represents the normal stress applied to the powder layer of metal soap, and τ represents the critical shear stress corresponding to the applied normal stress.) [2] A metal soap formulation comprising the metal soap described in [1] and other metal soaps, wherein the amount of the metal soap described in [1] is 50% by mass or more when the total amount of metal soaps contained in the metal soap formulation is taken as 100% by mass, and the pH of a 2% by mass aqueous dispersion of the metal soap formulation is 6.0 or more and 7.5 or less, and when the slope of the breakdown envelope of the metal soap formulation represented by the following formula (I) is A and the intercept is B, the values of A and B are within the following ranges. Equation (I): τ = Aσ + B 0.2 ≤ A ≤ 0.5 0.1 ≤ B ≤ 0.5 (In equation (I) above, σ represents the normal stress applied to the powder layer of the metal soap formulation, and τ represents the critical shear stress corresponding to the applied normal stress.) [3] A cosmetic containing the metal soap described in [1] or the metal soap formulation described in [2]. [4] A food additive containing the metal soap described in [1] or the metal soap formulation described in [2]. [5] A thermoplastic resin composition containing the metal soap of [1] or the metal soap formulation of [2]. [6] A method for producing the metal soap described in [1], comprising a preparation step of preparing an aqueous solution of a fatty acid alkali compound salt obtained by reacting 1.0 mole of a C6 to C24 fatty acid with a monovalent basic compound in a ratio of 0.9 moles to less than 1.0 mole, and an aqueous solution of a divalent metal salt, and a dropping step of dropping one of the two aqueous solutions into the other aqueous solution, A manufacturing method characterized in that, in the dropping step, the temperature of the aqueous solution to be dropped is maintained in the range of 0°C to 15°C, an amount equivalent to 50% to 55% by volume of the total amount of the aqueous solution to be dropped is dropped over 55 to 60 minutes, and the remaining amount equivalent to 45% to 50% by volume is dropped over 25 to 30 minutes. [Effects of the Invention]
[0010] The metal soap of the present invention can improve the performance of the addition target related to the purpose of adding the metal soap, not only make it difficult to degrade the performance other than the addition purpose, but also make it difficult to degrade the performance of the addition target even when the addition target is stored in a severe environment. Furthermore, the method of the present invention can produce the above metal soap of the present invention stably with high productivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] [Figure 1] This is a graph showing the failure envelopes of the metal soaps obtained in Examples 1 and 3 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF EMBODIMENTS FOR CARRYING OUT THE INVENTION
[0012] The metal soap of the present invention is a fatty acid metal soap having 6 to 24 carbon atoms, wherein a 2 mass% aqueous dispersion of the metal soap has a pH of 6.0 or more and 7.5 or less, and when the slope of the failure envelope represented by the following formula (I) of the metal soap is defined as A and the intercept is defined as B, the values of A and B are within the following ranges. Formula (I): τ=Aσ+B 0.2≦A≦0.5 0.1≦B≦0.5 (In the above formula (I), σ represents the normal stress applied to the powder layer of the metal soap, and τ represents the critical shear stress corresponding to the applied normal stress.)
[0013] Hereinafter, the preferred production method of the metal soap of the present invention, the properties of the obtained metal soap, the method of using the metal soap as an additive, and the product using the same will be described in detail. In addition, in the present specification, the numerical range defined by using the symbol "~" shall include the numerical values at both ends (upper limit and lower limit) of "~". For example, "2 to 5" represents 2 or more and 5 or less.
[0014] (1) Method for producing metal soap The metal soap of the present invention can be prepared by a double decomposition method in which a fatty acid alkali compound salt is reacted with a metal salt other than sodium or potassium. In particular, the metal soap of the present invention can be produced stably and productively by carrying out a double decomposition method including the following steps.
[0015] Step 1: A preparation step of preparing an aqueous solution of an alkali compound fatty acid obtained by reacting 1.0 mole of a fatty acid having 6 to 24 carbon atoms with a monovalent basic compound in a ratio of 0.9 moles to less than 1.0 mole, and an aqueous solution of a metal salt other than sodium or potassium, preferably an aqueous solution of a divalent metal salt. Step 2: A dropping step in which one of the prepared aqueous solutions of an alkali compound salt of a fatty acid and an aqueous solution of a metal salt is dropped dropwise into the other aqueous solution. In this step, the temperature of the aqueous solution to be dropped is maintained within a predetermined temperature range, and in the first half of the dropping step, approximately half of the total volume of the aqueous solution is dropped dropwise at a slower rate than in the second half, and in the second half of the dropping step, the remaining portion of the aqueous solution is dropped dropwise at a faster rate than in the first half, thereby forming a salt of a fatty acid having 6 to 24 carbon atoms with a metal other than sodium or potassium, preferably a salt with a divalent metal.
[0016] By reacting an aqueous solution of an alkali compound salt with an excess of fatty acids, obtained by reacting a fatty acid having 6 to 24 carbon atoms with a monovalent basic compound in the molar ratio within the specified range, with an aqueous solution of a metal salt other than sodium or potassium, the pH of the resulting metal soap, when dispersed in 2% by mass aqueous solution, can be set to 6.0 to 7.5. Furthermore, in the dropping step in which one aqueous solution of a fatty acid alkali compound salt and the other aqueous solution of a metal salt are dropped into the other aqueous solution, by maintaining the temperature of the dropping solution at a predetermined temperature and a predetermined dropping rate, the values of the slope A and intercept B of the fracture envelope of the obtained metal soap, represented by formula (I), can be set to the following ranges. Equation (I): τ = Aσ + B 0.2 ≤ A ≤ 0.5 0.1 ≤ B ≤ 0.5 (In equation (I) above, σ represents the normal stress applied to the powder layer of metal soap, and τ represents the critical shear stress corresponding to the applied normal stress.)
[0017] The fatty acids used as raw materials for fatty acid alkali compound salts are not particularly limited as long as they have 6 to 24 carbon atoms. That is, they may be naturally derived fatty acids or synthetic fatty acids, saturated fatty acids or unsaturated fatty acids, and linear or branched fatty acids. Furthermore, the fatty acid structure may contain hydroxyl groups, aldehyde groups, epoxy groups, etc. Preferably, they are linear fatty acids with 10 to 22 carbon atoms. If the number of carbon atoms is less than 6, the resulting metal soap will not be effective as a dispersant, and fatty acids with more than 24 carbon atoms are difficult to obtain industrially. These fatty acids may be used individually or in combination of two or more types.
[0018] Examples of the above fatty acids include caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, myristooleic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, arachidic acid, behenic acid, erucic acid, hydroxystearic acid, montanic acid, isostearic acid, 2-ethylhexanoic acid, and epoxystearic acid.
[0019] Examples of monovalent alkali compounds that can be used as raw materials for fatty acid alkali compound salts include hydroxides of alkali metals (such as sodium and potassium), ammonia, and amines such as triethylamine, monoethanolamine, diethanolamine, and triethanolamine. Because of their high solubility in water when used as fatty acid alkali compound salts, alkali metal hydroxides such as sodium and potassium are preferred.
[0020] The fatty acid alkali compound salts used in the present invention are obtained by reacting a monovalent basic compound in a ratio of 0.9 moles to less than 1 mole per 1.0 mole of a fatty acid having 6 to 24 carbon atoms, generally at a temperature above the melting point of the fatty acid and at a temperature at which the fatty acid does not decompose, preferably 100°C or lower, more preferably 50°C to 100°C, and even more preferably 80°C to 95°C.
[0021] In the present invention, divalent metal salts are preferred as metal salts other than sodium or potassium. Specifically, divalent metal salts are salts of a divalent inorganic metal with an inorganic acid or organic acid. Examples of divalent inorganic metals include alkaline earth metals such as magnesium, calcium, and barium, as well as titanium, zinc, iron, manganese, cadmium, mercury, zirconium, lead, copper, cobalt, and nickel. Of these, calcium, magnesium, barium, and zinc are preferred due to their readily available industrial availability. Calcium or magnesium are particularly preferred in terms of friction coefficient, tablet moldability, and stability of performance against temperature cycling. Examples of divalent metal salts include calcium chloride, calcium acetate, magnesium chloride, magnesium sulfate, copper sulfate, barium chloride, zinc chloride, and zinc sulfate. Chlorides, sulfates, and nitrates of calcium and magnesium are particularly preferred because they have good solubility in water and react efficiently with carboxylates.
[0022] Aqueous solutions of fatty acid alkali compound salts and aqueous solutions of metal salts other than sodium or potassium may contain water-soluble solvents other than water. Examples of water-soluble solvents other than water include methanol and ethanol.
[0023] In the dropping step, in which one aqueous solution of a fatty acid alkali compound salt and the other aqueous solution of a metal salt are dropped into the other aqueous solution, the temperature of the aqueous solution being dropped is set to a range of 0°C to 15°C, preferably to a range of 10°C to 15°C. The temperature of the aqueous solution receiving the drop is not particularly limited, but is preferably 50 to 100°C, more preferably 70 to 100°C, even more preferably 80 to 100°C, and most preferably 90 to 100°C. The temperature difference between the aqueous solution being added (T1) and the aqueous solution receiving it (T2), |T2-T1|, is preferably 35°C to 100°C, more preferably 55°C to 100°C, even more preferably 65°C to 100°C, and most preferably 75°C to 100°C. If the temperature difference is lower than this range, the slope A and intercept B of the breakdown envelope may fall outside the specified range, and if the temperature difference is higher than this range, the desired performance of the resulting metal soap as an additive may not be obtained.
[0024] In the first half of the dropping process, preferably, an amount equivalent to 50% to 55% by volume of the total volume of the aqueous solution to be dropped is added over 55 to 60 minutes; more preferably, an amount equivalent to 50% to 53% by volume of the aqueous solution to be dropped is added over 57 to 60 minutes; and even more preferably, an amount equivalent to 50% by volume of the aqueous solution is added over 60 minutes. In the latter half of the dropping process, preferably, an amount equivalent to 45% to 50% by volume of the total volume of the aqueous solution to be dropped is added over 25 to 30 minutes; more preferably, an amount equivalent to 47% to 50% by volume of the aqueous solution to be dropped is added over 27 to 30 minutes; and even more preferably, an amount equivalent to 50% by volume of the aqueous solution is added over 30 minutes.
[0025] When the above dropping rates are converted to the molar dropping rate of the solute contained in the aqueous solution, they roughly correspond to the following molar dropping rates. In the first half of the dropping process, when the total amount of fatty acid alkali compound salts or metal salts other than sodium or potassium contained in the aqueous solution being added is 1.0 mole, the rate is preferably 0.5 moles to 0.6 moles / hour, more preferably 0.5 moles / hour. In the second half of the dropping process, when the total amount of fatty acid alkali compound salts or metal salts other than sodium or potassium contained in the aqueous solution being added is 1.0 mole, the rate is preferably 1.0 mole / hour. If the dropping rate is too slow in the first half of the dropping process, the slope A and intercept B of the breakdown envelope may fall outside the specified range. If the dropping rate is too fast, the desired performance of the resulting metal soap as an additive may not be obtained. If the dropping rate is too slow in the latter half of the dropping process, the slope A and intercept B of the breakdown envelope may fall outside the specified range, and if the dropping rate is too fast, the desired performance of the resulting metal soap as an additive may not be obtained.
[0026] In the dropping step, where one aqueous solution of a fatty acid alkali compound salt and the other aqueous solution of a metal salt are added dropwise to the other aqueous solution, it is preferable to dropwise add the aqueous solution of a metal salt other than sodium or potassium to the fatty acid alkali compound salt aqueous solution. When dropping the fatty acid alkali compound salt aqueous solution, it is necessary to maintain the aqueous solution at 5 to 15°C, but this may cause the fatty acid alkali compound to precipitate, making handling complicated.
[0027] The concentration of the fatty acid alkali compound salt during metal soap production is typically 1% to 20% by mass, preferably 5% to 15% by mass, from the viewpoint of metal soap productivity and the handling properties of the fatty acid alkali compound salt aqueous solution or the resulting metal soap slurry. If the fatty acid alkali compound salt concentration is less than 1% by mass, the productivity of metal soap is low and it is not practically desirable. If it exceeds 20% by mass, the viscosity of the fatty acid alkali compound salt aqueous solution or the resulting metal soap slurry increases, making it difficult to carry out a uniform reaction. Furthermore, the concentration of the metal salt in an aqueous solution of a metal salt other than sodium or potassium is usually 1% to 50% by mass, preferably 10% to 40% by mass, from the viewpoint of the productivity of metal soap production and the handling of the aqueous solution of the metal salt other than sodium or potassium or the resulting metal soap slurry.
[0028] When a divalent metal other than sodium or potassium is used as the metal salt, the reaction between the fatty acid alkali compound salt and the divalent metal salt is preferably carried out in a ratio of 0.45 to 0.7 moles of the divalent metal salt per mole of monovalent alkali compound used to obtain the fatty acid alkali compound salt. A more preferable ratio of divalent metal salt is 0.49 to 0.6 moles, and an even more preferable ratio is 0.49 to 0.55 moles.
[0029] By drying the metal soap slurry obtained by the above method, the metal soap powder of the present invention can be obtained. The metal soap slurry is dried either as is, or after the solvent is separated using a centrifugal dehydrator, filter press, vacuum rotary filter, etc., and if necessary, washing is performed to remove by-product inorganic salts, and then it is dried using a rotary dryer, airflow dryer, aeration dryer, spray dryer, fluidized bed dryer, etc. The drying method may be continuous or batch, and under atmospheric pressure or vacuum.
[0030] (2) pH of aqueous dispersion of metal soap The metal soap of the present invention is characterized in that the pH of the metal soap when dispersed in a 2% by mass aqueous dispersion is not alkaline. Specifically, the pH of the metal soap when dispersed in a 2% by mass aqueous dispersion is in the range of 6.0 to 7.5. A metal soap with a pH in the range of 6.0 to 7.5 when dispersed in a 2% by mass aqueous dispersion can improve the performance of the target to which the metal soap is added, and can also prevent deterioration of the performance of other substances. The obtained metal soap may be used alone, or it may be used in combination with metal soaps containing different metals.
[0031] The pH measurement value in this invention is the pH of a metal soap aqueous dispersion prepared by dispersing metal soap in ion-exchanged water to a concentration of 2% by mass using a nonionic surfactant that does not affect pH. Examples of the above nonionic surfactant include polyethylene glycol-based nonionic surfactants with an HLB of 12 to 15, and from the viewpoint of dispersion stability, those with an HLB of about 13, such as polyoxyethylene (10 mol) nonylphenol ether or polyoxyethylene (9 mol) tridecyl ether, are preferred.
[0032] (3) Destruction envelope of metallic soap In the present invention, when the slope of the fracture envelope of the metal soap represented by the following formula (I) is A and the intercept is B, the values of A and B satisfy the following conditions. Equation (I): τ = Aσ + B 0.2 ≤ A ≤ 0.5 0.1 ≤ B ≤ 0.5 (In equation (I) above, σ represents the normal stress applied to the powder layer of metal soap, and τ represents the critical shear stress corresponding to the applied normal stress.) A metal soap whose fracture envelope slope A and intercept B satisfy the conditions of formula (I) above can reduce the degradation of the properties of the substance to which it is added, even when the substance is stored under harsh conditions. Specifically, it can reduce fluctuations in the properties of the substance to which it is added under conditions of load and shear stress.
[0033] The fracture envelope is a line obtained by applying a shear stress (τ) to an arbitrary surface in a stationary powder layer while applying a normal stress (σ) to it, gradually increasing the shear stress (critical shear stress) at which the surface begins to collapse, measuring the shear stress at which it reaches a critical stress state for multiple normal stresses (σ), and plotting the measurement results (i.e., a combination of a specific σ value and a corresponding specific τ value) on the σ-τ plane.
[0034] In general, the fracture envelope of a powder can be expressed by the following equation (II). Equation (II): τ = C + σ tanφ (In equation (II) above, σ represents the normal stress applied to the powder layer, τ represents the critical shear stress at which shear occurs under the applied normal stress (i.e., the shear strength of the test specimen), C represents the cohesion, and φ represents the internal friction angle (shear resistance angle).) In equation (I), which represents the fracture envelope of a metal soap, the slope A corresponds to tanφ (the tangent value of the internal friction angle), and the intercept B corresponds to the cohesion force C.
[0035] The fracture envelope of a powder can be created by (i) placing a stationary powder layer of a powder sample inside a powder rheometer (for example, a powder rheometer FT-4 manufactured by Freeman Technology), applying a normal stress (σ) to the stationary powder layer while gradually increasing it to a predetermined value, and rotating the shear blade, measuring the shear stress (τ) at the time of shear initiation at each stage of normal stress (σ), and (iii) plotting the measurement results at each stage of normal stress (σ) on a graph with the value of the normal stress σ on the X axis and the value of the shear stress τ on the Y axis. In this invention, the above shear test is performed using a powder sample of metal soap, and the obtained measurement results (i.e., measured values σ and τ) are applied to the above formula representing the fracture envelope to determine the slope of the approximate straight line, which is defined as A, and the intercept of the approximate straight line on the Y axis is defined as B (shear stress when the normal stress is 0). Preferably, the approximate straight line of the fracture envelope is determined based on the portion of the fracture envelope corresponding to the powder layer fracture envelope (PYL). More specifically, it is preferable to determine it based on a fracture envelope created in the range of normal stress (X axis) of 5 to 9 kPa and shear stress (Y axis) of 1 to 9 kPa. Typically, the residual between the measurement result and the approximate curve is minimized by the least squares method.
[0036] (4) Properties of metal soap powder With regard to the average particle size of the metal soap of the present invention, it is preferable that the volume-average diameter (50% cumulative diameter (D50) on a volume basis) is in the range of 10 to 20 μm, from the viewpoint of keeping the slope A and intercept B of the fracture envelope represented by the above formula (I) within the above range. Furthermore, the metal soap of the present invention preferably has a particle size summary value A within the specific range shown below. The particle size summary value A is an index related to the variation in particle size. Specifically, the particle size summary value A can be obtained from the following formula. Granularity summary value A = (D90 - D10) / D50 D10: 10% cumulative diameter (μm) of metallic soap particles based on volume. D50: 50% cumulative diameter (μm) of metallic soap particles based on volume. D90: 90% cumulative diameter (μm) of metallic soap particles based on volume. The particle size summary value A can be calculated from the cumulative diameter based on volume. The particle size summary value A is preferably between 1 and 3, and more preferably between 1 and 2.
[0037] (5) Use as an additive The metal soap of the present invention can be used as an additive in a wide range of industrial fields. When the metal soap of the present invention is added to a product, it can improve the performance related to the purpose of addition, and does not easily degrade the performance of other products. Furthermore, even when a product to which the metal soap of the present invention has been added is stored under harsh conditions, the performance of the product does not easily deteriorate. Furthermore, metal soap formulations combining the metal soap of the present invention with other metal soaps and non-metal soap components that do not satisfy the above-described conditions for the fracture envelope can also be used as additives, provided that they contain the metal soap of the present invention as the main component and are within a range of composition that maintains the same effects as the metal soap of the present invention. Specifically, a metal soap formulation containing the metal soap of the present invention and other metal soaps can be used as an additive in the same way as when using the metal soap of the present invention alone, provided that when the total amount of metal soaps contained in the formulation is taken as 100% by mass, the amount of the metal soap of the present invention is 50% by mass or more, preferably 60% by mass or more, and the pH of a 2% by mass aqueous dispersion of the metal soap formulation is 6.0 or more and 7.5 or less, and when the slope of the breakdown envelope of the metal soap formulation represented by the following formula (I) is A and the intercept is B, the values of A and B are within the following ranges. Equation (I): τ = Aσ + B 0.2 ≤ A ≤ 0.5 0.1 ≤ B ≤ 0.5 (In equation (I) above, σ represents the normal stress applied to the powder layer of the metal soap formulation, and τ represents the critical shear stress corresponding to the applied normal stress.) The metal soap of the present invention can be used, for example, as an additive in cosmetics, food products, and thermoplastic resin compositions.
[0038] (i) Use in cosmetics The metal soap of the present invention can be used as a cosmetic additive for purposes such as improving adhesion and spreadability to the skin, improving the finish and durability of cosmetics, and improving pigment dispersibility. Furthermore, because it has little effect on the components of cosmetics, for example, cosmetics containing the metal soap of the present invention do not change in color tone due to deterioration of colorants during storage and have storage stability. Furthermore, cosmetics containing the metal soap of the present invention are less likely to deteriorate even when stored in harsh environments where low temperature and low humidity conditions are repeatedly alternating with high temperature and high humidity conditions. For example, makeup cosmetics containing the metal soap of the present invention are less likely to change color even when stored in environments where temperatures are repeatedly alternating between 0°C, 10% RH and 40°C, 90% RH conditions.
[0039] Cosmetics that may use the metal soap of the present invention include skincare cosmetics such as facial cleansing creams, lotions, massage creams, emulsions, and moisturizing creams; makeup cosmetics such as foundations, lipsticks, and blushes; body care cosmetics such as bath additives, sunscreens, and deodorant sprays; and hair care cosmetics such as shampoos, conditioners, hair liquids, and hair dyes. In addition to the metal soap of the present invention, other known cosmetic ingredients such as organic or inorganic pigments, fragrances, oils and fats, waxes, hydrocarbons, higher fatty acids, higher alcohols, esters, silicone oils, surfactants such as nonionic, anionic, cationic, and amphoteric surfactants, humectants, UV absorbers, and antioxidants may be used as appropriate.
[0040] (ii) Use as a food additive The metal soap of the present invention can be used as a food additive for purposes such as improving moldability, fluidity, preventing caking, reducing hygroscopicity, and improving texture. Furthermore, because it has little effect on food, food containing the metal soap of the present invention, for example, does not fade or discolor, has storage stability, and is excellent in terms of food safety. Moreover, food containing the metal soap of the present invention is less likely to deteriorate even when stored in harsh environments where low temperature and low humidity conditions are alternately followed by high temperature and high humidity conditions. For example, food containing the metal soap of the present invention is less likely to change color even when stored in an environment where 10% RH conditions and 40°C, 90% RH conditions are alternately followed by a change in color.
[0041] Examples of foods to which the metal soap of the present invention may be added include cereal powders such as wheat flour and starch, premixes made by blending cereal powder with butter and sugar, spices such as chili peppers and seasonings such as monosodium glutamate, extracts from citrus peels, food colorings such as red perilla, noodles such as udon, bakery foods such as sliced bread, fried foods such as donuts, and confectionery such as biscuits, candies, and chewing gum. In addition to the metal soap of the present invention, other food additives such as sweeteners, colorants, preservatives, thickeners and stabilizers, antioxidants, bittering agents, glazing agents, acidulants, seasonings, emulsifiers, leavening agents, and fortifiers may be used as appropriate.
[0042] (iii) Use in thermoplastic resin compositions The metal soap of the present invention can be used as an additive for thermoplastic resins, for example, to improve the dispersibility of pigments and fillers, and has little effect on the thermoplastic resin itself or the components of the thermoplastic resin composition. For example, a thermoplastic resin composition containing the metal soap of the present invention is less likely to experience a decrease in the molecular weight of the thermoplastic resin or yellowing of phenolic antioxidants. Furthermore, the thermoplastic resin composition containing the metal soap of the present invention is less prone to deterioration of the thermoplastic resin itself or the thermoplastic resin composition even when stored in harsh environments of high temperature and high humidity. For example, molded articles of the thermoplastic resin composition containing the metal soap of the present invention do not deteriorate in abrasion resistance and scratch resistance even when stored in environments of high temperature and high humidity such as 40°C and 95%RH. [Examples]
[0043] The present invention will be described in more detail below with reference to examples and comparative examples. (1) Manufacturing and evaluation of metal soaps [Manufacturing example] <Example 1> 250 g (0.88 mol) of stearic acid and 2500 g of water were placed in a 3 L glass separable flask and heated to 90°C. Next, 69.7 g (0.84 mol; equivalent to 0.95 mol per mol of fatty acid) of 48% sodium hydroxide aqueous solution was added and the mixture was stirred at the same temperature (90°C) for 1 hour. Then, while maintaining the temperature at 90°C, half of 140.4 g (0.44 mol; equivalent to 0.50 mol (1.00 equivalent) per mol of fatty acid) of 10°C 35% calcium chloride aqueous solution was added dropwise over 1 hour, and the remaining half was added dropwise over 30 minutes. After the dropwise addition was complete, the mixture was stirred for another hour at 90°C. 1500 g of water was added to the resulting fatty acid calcium slurry and the mixture was cooled to below 65°C. The mixture was then filtered using a suction filter, washed twice with 1000g of water, and dried at 65°C for 48 hours using a forced-air dryer to obtain the metal soap (calcium stearate) of Example 1.
[0044] <Example 2> In a 3L glass separable flask, 176g (0.88 mol) of lauric acid and 1760g of water were charged and heated to 90°C. Next, 69.7g (0.84 mol; equivalent to 0.95 mol per mol of fatty acid) of 48% sodium hydroxide aqueous solution was added, and the mixture was stirred at the same temperature (90°C) for 1 hour. Then, while maintaining the temperature at 90°C, half of 140.4g (0.44 mol; equivalent to 0.50 mol (1.00 equivalent) per mol of fatty acid) of 10°C 35% calcium chloride aqueous solution was added dropwise over 1 hour, and the remaining half was added dropwise over 30 minutes. After the dropwise addition was complete, the mixture was stirred for another hour at 90°C. 1500g of water was added to the resulting fatty acid calcium slurry, and the mixture was cooled to below 65°C. The mixture was then filtered using a suction filter, washed twice with 1000g of water, and dried at 65°C for 48 hours using a forced-air dryer to obtain the metal soap (calcium laurate) of Example 2.
[0045] <Example 3> 250 g (0.88 mol) of stearic acid and 2500 g of water were placed in a 3 L glass separable flask and heated to 90°C. Next, 69.7 g (0.84 mol; equivalent to 0.95 mol per mol of fatty acid) of 48% sodium hydroxide aqueous solution was added and the mixture was stirred at the same temperature (90°C) for 1 hour. Then, while maintaining the temperature at 90°C, half of 213.3 g (0.44 mol; equivalent to 0.50 mol (1.00 equivalent) per mol of fatty acid) of 25% magnesium sulfate aqueous solution at 10°C was added dropwise over 1 hour, and the remaining half was added dropwise over 30 minutes. After the dropwise addition was complete, the mixture was stirred for another hour at 90°C. 1500 g of water was added to the resulting fatty acid magnesium slurry and the mixture was cooled to below 65°C. The mixture was then filtered using a suction filter, washed twice with 1000g of water, and dried at 65°C for 48 hours using a forced-air dryer to obtain the metal soap (magnesium stearate) of Example 3. <Example 4> 250 g (0.88 mol) of stearic acid and 2500 g of water were placed in a 3 L glass separable flask and heated to 90°C. Next, 69.7 g (0.84 mol; equivalent to 0.95 mol per mol of fatty acid) of 48% sodium hydroxide aqueous solution was added and the mixture was stirred at the same temperature (90°C) for 1 hour. Then, while maintaining the temperature at 90°C, half of 284.2 g (0.44 mol; equivalent to 0.50 mol (1.00 equivalent) per mol of fatty acid) of 10°C 25% zinc sulfate aqueous solution was added dropwise over 1 hour, and the remaining half was added dropwise over 30 minutes. After the dropwise addition was complete, the mixture was stirred for another hour at 90°C. 1500 g of water was added to the resulting fatty acid zinc slurry and the mixture was cooled to below 65°C. The mixture was then filtered using a suction filter, washed twice with 1000g of water, and dried at 65°C for 48 hours using a forced-air dryer to obtain the metal soap (zinc stearate) of Example 4.
[0046] <Comparative Example 1> 250 g (0.88 mol) of stearic acid and 2500 g of water were placed in a 3 L glass separable flask and heated to 90°C. Next, 74.8 g (0.90 mol; equivalent to 1.02 mol per mol of fatty acid) of 48% sodium hydroxide aqueous solution was added and the mixture was stirred at the same temperature (90°C) for 1 hour. Then, while maintaining the temperature at 90°C, 142.4 g (0.45 mol; equivalent to 0.51 mol (1.02 equivalents) of 35% calcium chloride aqueous solution at 30°C was added dropwise over 1 hour. After the addition was complete, the mixture was stirred for another hour at 90°C. 1500 g of water was added to the resulting fatty acid calcium slurry and cooled to below 65°C. The mixture was then filtered using a suction filter, washed twice with 1000 g of water, and dried in a forced-air dryer at 65°C for 48 hours to obtain the metal soap (calcium stearate) of Comparative Example 1.
[0047] <Comparative Example 2> A 3L glass separable flask was charged with 250 g (0.88 mol) of stearic acid and 2500 g of water, and the temperature was raised to 90°C. Next, 74.8 g (0.90 mol; equivalent to 1.02 mol per 1 mol of fatty acid) of a 48% aqueous sodium hydroxide solution was added, followed by stirring at the same temperature (90°C) for 1 hour. Thereafter, while maintaining the temperature at 90°C, 216.2 g (0.45 mol; equivalent to 0.51 mol (1.02 equivalents) per 1 mol of fatty acid) of a 25% aqueous magnesium sulfate solution at 30°C was added dropwise over 1 hour. After completion of the dropwise addition, the mixture was further stirred at 90°C for 1 hour. 1500 g of water was added to the obtained fatty acid magnesium slurry, and the mixture was cooled to 65°C or lower. Thereafter, the mixture was filtered with a suction filter, washed twice with 1000 g of water, and dried at 65°C for 48 hours using a forced-air dryer to obtain the metal soap (magnesium stearate) of Comparative Example 2. <Comparative Example 3> A 3L glass separable flask was charged with 250 g (0.88 mol) of stearic acid and 2500 g of water, and the temperature was raised to 90°C. Next, 74.8 g (0.90 mol; equivalent to 1.02 mol per 1 mol of fatty acid) of a 48% aqueous sodium hydroxide solution was added, followed by stirring at the same temperature (90°C) for 1 hour. Thereafter, while maintaining the temperature at 90°C, half of 290.6 g (0.45 mol; equivalent to 0.51 mol (1.02 equivalents) per 1 mol of fatty acid) of a 25% aqueous zinc sulfate solution at 10°C was added dropwise over 1 hour, and the remaining half was added dropwise over 30 minutes. After completion of the dropwise addition, the mixture was further stirred at 90°C for 1 hour. 1500 g of water was added to the obtained fatty acid zinc slurry, and the mixture was cooled to 65°C or lower. Thereafter, the mixture was filtered with a suction filter, washed twice with 1000 g of water, and dried at 65°C for 48 hours using a forced-air dryer to obtain the metal soap (zinc stearate) of Comparative Example 3.
[0048] [Evaluation Methods] <pH Measurement> An aqueous dispersion containing 2% by mass of metal soap was prepared using an aqueous solution containing 0.2% by mass of a nonionic surfactant (Nonion NS-210 (product name) manufactured by NOF Corporation), and the pH at 25°C was measured.
[0049] <Identification of Fracture Envelope> (i) Equipment Used Freeman Technology FT-4 Powder Rheometer (ii) Shear test A container with a capacity of 85 mL was filled with powder, and the rotor blade was moved back and forth once from the top to the bottom of the container. After compaction at 15 kPa for 60 seconds using a compaction jig, the excess powder overflowing from the opening of the container was scraped off. The stress at which shear occurred was measured while applying normal stresses of 9 kPa, 8 kPa, 7 kPa, 6 kPa, or 5 kPa, and rotating the shear blade at 18° / min. The stress at which shear occurred measured at each normal stress was plotted on a graph with the normal stress on the X axis and the stress at which shear occurred on the Y axis. A fracture envelope was created by linear approximation from the plotted data, and the slope A and intercept B (shear stress when the normal stress is 0) were calculated. Furthermore, for fracture envelopes created with normal stress (X-axis) in the range of 5-9 kPa and shear stress (Y-axis) in the range of 1-9 kPa, the slope A and intercept B were read.
[0050] <Measurement of average particle size> The average particle size of the metal soaps in the examples and comparative examples was measured as follows: 2.0 g of each metal soap from the examples and comparative examples was placed in a 100 mL glass beaker, and 100 mL of ethanol was added to prepare the sample. The sample was supplied to a particle size distribution analyzer ("Microtrac MT-3000", Microtrac-Bell Co., Ltd.) to measure the particle size (principle: laser diffraction and scattering method). When an integrated distribution curve was created with the total volume of the powder sample being measured as 100%, the average particle size at the point corresponding to 50% of the integrated distribution curve was determined.
[0051] The evaluation results of the metal soaps obtained in the examples and comparative examples are shown in Table 1. The fracture envelopes of each metal soap are shown in Figure 1. The metal soaps of Examples 1 to 4 had a pH in the range of 6.0 to 7.5 for an aqueous dispersion containing 2% by mass of the metal soap, and the slope A and intercept B of the fracture envelope were in the range of 0.2 ≤ A ≤ 0.5 and 0.1 ≤ B ≤ 0.5, respectively. Furthermore, the metal soaps of Examples 1 to 4 had a volume-average diameter in the range of 10 to 20 μm, and a particle size summary value A was between 1 and 3. On the other hand, the metal soaps of Comparative Examples 1 to 3 showed alkalinity, with the pH of the aqueous dispersion containing 2% by mass of the metal soap being greater than 7.5, the slope A of the fracture envelope being greater than 0.5, and the intercept B being greater than 0.5. Furthermore, the metal soaps of Comparative Examples 1 to 3 had a volume-average diameter greater than 20 μm and a particle size summary value A greater than 3.
[0052] [Table 1]
[0053] (2) Preparation and evaluation of cosmetics Using the metal soaps from each example and comparative example, compositions were prepared by mixing the substances shown in the formulation column of Table 2 in predetermined proportions. These compositions were then poured into molds to form lipstick-like makeup cosmetics, and the following items were evaluated. Furthermore, the obtained lipsticks were subjected to an accelerated cycling test, in which they were stored for one month in an atmosphere where low temperature and low humidity conditions (0°C, 10%RH) and high temperature and high humidity conditions (40°C, 90%RH) were alternated every week. The same items were then evaluated to confirm whether the performance had deteriorated compared to before the test.
[0054] <Adhesion> Twenty women (ages 20-35) served as panelists, and each panelist scored the application of makeup products to their skin according to the following criteria. Products with a total score of 30 points or higher were evaluated as having good skin adhesion. 2. If you feel it adheres well to your skin. 1 point: If you feel that it doesn't adhere to the skin very well. 0 points: If you felt that it didn't adhere well to your skin.
[0055] <Spreadability> Twenty women (ages 20-35) served as panelists, and each panelist scored the spreadability of makeup products using the following criteria. Products with a total score of 30 points or higher were evaluated as having good spreadability (spreadability) when applied. 2. If you feel that the cosmetic product spreads well when you use it. 1 point: If you feel that the cosmetic product does not spread very well when you use it. 0 points: If you felt that the cosmetic product did not spread well when used.
[0056] <Uneven makeup color> Twenty women (ages 20-35) served as panelists, and each panelist scored the finish achieved when using makeup products according to the following criteria. A total score of 30 points or higher was considered to indicate a good finish when using the product. 2 points: If you feel the finish is good with no uneven coloring. 1 point: If you feel there is some unevenness in color and the finish is slightly poor. 0 points: If you feel the finish is poor due to uneven coloring.
[0057] <Sustainability> Twenty women (ages 20-35) served as panelists. Each panelist scored the condition of the makeup product four hours after application, according to the following criteria. Products with a total score of 30 points or higher were evaluated as having good staying power. 2 points: If you feel that there is no color shift and no makeup breakdown. 1 point: If you feel that the color is slightly uneven or that your makeup is slightly smudged. 0 points: If you feel that your makeup has clearly smudged or worn off.
[0058] Table 2 shows the evaluation results of the cosmetics obtained in the examples and comparative examples. The cosmetic compositions of Examples 5 to 8 (metal soaps of Examples 1 to 4) all scored 30 points or higher in all evaluation items during manufacturing and were evaluated as good. Furthermore, the cosmetic compositions of Examples 5 to 8 also scored 30 points or higher in all evaluation items after accelerated cycling tests involving severe environmental changes and were evaluated as good. On the other hand, the cosmetics of Comparative Examples 4 and 6 (metal soaps of Comparative Examples 1 and 3) scored less than 30 points in durability during manufacturing, and all evaluation items after the accelerated cycling test also scored less than 30 points. The cosmetic of Comparative Example 5 (metal soap of Comparative Example 2) scored 30 points or higher in all evaluation items during manufacturing and was evaluated as good, but all evaluation items after the accelerated cycling test scored less than 30 points. Based on the above evaluation results, it was confirmed that the cosmetic composition of the example was less prone to deterioration than the cosmetic composition of the comparative example, even when stored under harsh conditions.
[0059] [Table 2]
[0060] (3) Preparation and evaluation of food 450g of red perilla powder, 40g of crystalline cellulose, and 10g of the metal soap from each example and comparative example were added and mixed using a high-speed mixer to prepare a powdered food composition. 150 tablets of this food composition were made using a single-type tablet press with a 10mm diameter mold, and the moldability was evaluated according to the following criteria. Furthermore, the obtained powdered food composition was subjected to an accelerated cycling test in which it was stored for one month in an atmosphere where low temperature and low humidity (0°C, 10%RH) conditions and high temperature and high humidity (40°C, 90%RH) conditions were alternated every week. After that, its appearance was observed according to the following criteria.
[0061] <Moldability> ○: No creaking during the molding of 150 tablets, and no surface sticking or capping is observed in the tablets after molding 150 tablets. △: Although there is no creaking during molding, surface sticking is observed in the tablets after molding 150 tablets. ×: If creaking occurs immediately after molding, making molding impossible.
[0062] <Visual Inspection> ○: When little to no discoloration is observed after the storage test. ×: If the discoloration is clearly visible after the storage test.
[0063] Table 3 shows the evaluation results of the foods obtained in the examples and comparative examples. The food products of Examples 9 to 12 (metal soaps of Examples 1 to 4) were evaluated as having good moldability during manufacturing. Furthermore, the food products of Examples 9 to 12 showed almost no discoloration after accelerated cycling tests involving severe environmental changes. On the other hand, the foods of Comparative Examples 7 and 8 (containing the metal soaps of Comparative Examples 1 and 2) were evaluated as having good moldability during manufacturing, while the food of Comparative Example 9 (containing the metal soap of Comparative Example 3) was evaluated as having somewhat poor moldability during manufacturing, and the food of Comparative Example 10 (without metal soap) was evaluated as having poor moldability during manufacturing. Furthermore, the foods of Comparative Examples 7 to 10 (containing the metal soaps of Comparative Examples 1 to 3 and without metal soap) clearly discolored after accelerated cycling tests involving severe environmental changes. Based on the above evaluation results, it was confirmed that the food product in the example was less prone to deterioration than the food product in the comparative example, even when stored under harsh conditions.
[0064] [Table 3]
[0065] (4) Preparation and evaluation of thermoplastic resin compositions A polyolefin resin (olefin / alkene elastomer (product name: Ultrasen 685, manufactured by Tosoh Corporation)) was mixed with 0.5 wt% of the metal soaps listed in Table 1, and the resulting mixture was kneaded using a kneader (Toyo Seiki Seisakusho Laboplast Mill 4C150-01) at a temperature of 210°C, a rotation speed of 80 rpm, and a time of 5 minutes. After the thermoplastic resin composition was removed from the kneader and placed in a mold to create a 5cm x 5cm x 5mm test specimen, the coefficient of friction (low load), coefficient of friction (high load), and scratch resistance were evaluated using this test specimen. Furthermore, after conducting an accelerated test in which the obtained test specimens were left under high temperature and high humidity conditions (40°C, 90%RH) for two weeks, the same items were evaluated to confirm whether the performance had deteriorated compared to before the test.
[0066] <Coefficient of friction> The coefficient of friction was measured using a Bowden testing machine. First, a 1 cm long semi-cylindrical stainless steel element was applied to the test specimen in line contact with the specimen under the conditions of load: 100 g, speed: 2.5 mm / s, and measurement distance: 10 mm to measure the coefficient of friction (low load). Next, a 3 mm diameter steel ball was applied to the same test specimen in point contact with the specimen under the conditions of load: 500 g, speed: 2.5 mm / s, and measurement distance: 10 mm to measure the coefficient of friction (high load), and evaluated according to the following criteria. <Evaluation criteria for coefficient of friction (low load)> ◎: Less than 0.4, ○: 0.4 or higher and less than 0.5, ×: 0.5 or higher <Evaluation criteria for coefficient of friction (high load)> ◎: Less than 0.3, ○: 0.3 or higher and less than 0.4, ×: 0.4 or higher
[0067] <Coefficient of friction> The wear depth (in μm) of the specimen surface after high-load testing was measured using a contact-type film thickness gauge and evaluated according to the following criteria. <Criteria for evaluating scratch resistance> ◎: Less than 3.5 μm, ○: 3.5 μm or larger and less than 4.0 μm, ×: 4.0μm or more
[0068] The evaluation results of the thermoplastic resin compositions obtained in the examples and comparative examples are shown in Tables 4-1 and 4-2. The thermoplastic resin compositions of Examples 13 to 16 (metal soaps of Examples 1 to 4) exhibited low coefficients of friction (low load) and high load) on the test specimens, as well as excellent scratch resistance, suggesting that the molecular weight of the thermoplastic resin was less likely to decrease. Furthermore, the thermoplastic resin compositions of the examples showed no degradation even after accelerated cycling tests, as they maintained low coefficients of friction (low load) and high load) on the test specimens and exhibited excellent scratch resistance. On the other hand, the thermoplastic resin compositions of Comparative Examples 11 to 13 (metal soaps of Comparative Examples 1 to 3) were evaluated as unsatisfactory, exhibiting high coefficients of friction (low load) and high load, as well as low scratch resistance, both immediately after manufacturing and after accelerated cycling tests. Based on the above evaluation results, it was confirmed that the thermoplastic resin composition of the example is less prone to degradation than the thermoplastic resin composition of the comparative example, even when stored under harsh conditions.
[0069] [Table 4]
Claims
1. A metal soap having 6 to 24 carbon atoms, wherein the pH of a 2% by mass aqueous dispersion of the metal soap is 6.0 or higher and 7.5 or lower, and when the slope of the breakdown envelope of the metal soap represented by the following formula (I) is A and the intercept is B, the values of A and B are within the following ranges. Formula (I): τ=Aσ+B 0.2 ≤ A ≤ 0.5 0.1 ≤ B ≤ 0.5 (In equation (I) above, σ represents the normal stress applied to the powder layer of metal soap, and τ represents the critical shear stress corresponding to the applied normal stress.)
2. A metal soap formulation comprising the metal soap described in claim 1 and other metal soaps, wherein when the total amount of metal soaps contained in the metal soap formulation is taken as 100% by mass, the amount of the metal soap described in claim 1 is 50% by mass or more, and the pH of a 2% by mass aqueous dispersion of the metal soap formulation is 6.0 or more and 7.5 or less, and when the slope of the breakdown envelope of the metal soap formulation represented by the following formula (I) is A and the intercept is B, the values of A and B are within the following ranges. Formula (I): τ=Aσ+B 0.2 ≤ A ≤ 0.5 0.1 ≤ B ≤ 0.5 (In equation (I) above, σ represents the normal stress applied to the powder layer of the metal soap formulation, and τ represents the critical shear stress corresponding to the applied normal stress.)
3. A cosmetic composition containing the metal soap described in claim 1 or the metal soap formulation described in claim 2.
4. A food additive containing the metal soap described in claim 1 or the metal soap formulation described in claim 2.
5. A thermoplastic resin composition containing the metal soap described in claim 1 or the metal soap formulation described in claim 2.
6. A method for producing a metal soap according to claim 1, comprising a preparation step of preparing an aqueous solution of a fatty acid alkali compound salt obtained by reacting 1.0 mole of a fatty acid having 6 to 24 carbon atoms with a monovalent basic compound in a ratio of 0.9 moles to less than 1.0 mole, and an aqueous solution of a divalent metal salt, and a dropping step of dropping one of the two aqueous solutions into the other aqueous solution, A manufacturing method characterized in that, in the dropping step, the temperature of the aqueous solution to be dropped is maintained in the range of 0°C to 15°C, an amount equivalent to 50% to 55% by volume of the total amount of the aqueous solution to be dropped is dropped over 55 to 60 minutes, and the remaining amount equivalent to 45% to 50% by volume is dropped over 25 to 30 minutes.
Citation Information
Patent Citations
Metallic soap for cosmetic and method for producing the same
JP2007186463A
Thermoplastic resin composition
WO2006006727A1
Metal soap for addition to food and process for production thereof
WO2007013655A1